2020
DOI: 10.1002/wcc.691
|View full text |Cite
|
Sign up to set email alerts
|

Climate and society in European history

Abstract: This article evaluates 165 studies from various disciplines, published between 2000 and 2019, which in different ways link past climate variability and change to human history in medieval and early modern Europe (here, c. 700–1815 CE). Within this review, we focus on the identification and interpretation of causal links between changes in climate and in human societies. A revised climate–society impact order model of historical climate–society interactions is presented and applied to structure the findings of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 193 publications
(311 reference statements)
0
40
0
Order By: Relevance
“…The influence of long-term climate variability on early modern grain yields and prices, and more generally on the economy, has for a long time been a matter of contrasting views. Positions in historical scholarship have ranged from climate determinism to, more commonly, an outright rejection of detectable climate influences (for a review, see Ljungqvist et al 2021). A pioneering study by Brückner (1895), covering the eighteenth and nineteenth centuries, concluded that higher rainfall decreased grain yields and increased grain prices in western and central Europe, whereas the opposite was observed in eastern Europe, promoting climate-influenced grain trade patterns and policies.…”
Section: Climate Variability and Grain Prices In Early Modern Europementioning
confidence: 99%
See 2 more Smart Citations
“…The influence of long-term climate variability on early modern grain yields and prices, and more generally on the economy, has for a long time been a matter of contrasting views. Positions in historical scholarship have ranged from climate determinism to, more commonly, an outright rejection of detectable climate influences (for a review, see Ljungqvist et al 2021). A pioneering study by Brückner (1895), covering the eighteenth and nineteenth centuries, concluded that higher rainfall decreased grain yields and increased grain prices in western and central Europe, whereas the opposite was observed in eastern Europe, promoting climate-influenced grain trade patterns and policies.…”
Section: Climate Variability and Grain Prices In Early Modern Europementioning
confidence: 99%
“…The impact of climate variability on grain prices is likely mitigated by different adaptation strategies making grain agriculture more resilient to climate fluctuations . A growing body of literature has shown how farming, and society at large, in early modern Europe adopted and adjusted to climatic change and variability [for a review, see Ljungqvist et al (2021)]. Cultivation at various elevations and sites with different soil properties and climate sensitivities along with a growing diversification of grain crops altered climate resilience.…”
Section: Climate Adaptation Of Agriculture and The Effects Of Market mentioning
confidence: 99%
See 1 more Smart Citation
“…Even comparably small changes in temperature and precipitation can result in measurable impacts on diseases [ 2 ]. Although many health risks are associated with secondary climatic influences, such as shifting patterns of disease vectors or affects on food production, water supplies, social disruption, and migration [ 3 5 ], climate is ranked as one of the most important drivers of infectious disease [ 6 ]. Hence, studies of human health vulnerability in relation to changing climate or extreme weather events need to include both direct and indirect impacts of climate change [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in malaria transmission has been mainly attributed to improved socioeconomic conditions, which included better healthcare (the increase in treatment of quinine [ 43 ]) and better hygiene conditions (draining of wetlands [ 34 ]). Although it has been speculated that the comparably low summer temperatures during the eighteenth and nineteenth centuries perhaps also played a role in the long-term decline in malaria transmission [ 43 , 44 ], this explanation appears highly questionable since palaeoclimate records show even colder conditions during the seventeenth century [ 5 , 45 , 46 ]. Notably, long-term warming at higher latitudes have not shown decisive influences on malaria dynamics in the long run [ 29 , 36 ] as has been predicted by some malaria models [ 47 ].…”
Section: Introductionmentioning
confidence: 99%